POTRET MODEL PENGELOLAAN PENDIDIKAN UNKLUSI : Studi Kasus Implementasi di Sekolah Dasar - Nurwahidah; Nur Ilma Kusjayanti; Muh. Fadhl Al-Jentak; Ahlun Ansar; Arismunandar (STKIP Subang, 2026)
Education is a fundamental right for every citizen, including children with special needs (ABk), which is expressly mandated in Law no. 20 of 2003 concerning the national education system. This study was designed to delve deeper into the implementation of inclusive education at the UPT SPF SDN IKIP I Makassar City. Using a descriptive qualitative approach, data were collected through semi-structured interviews with the principal and class teachers who handle students with special needs (ABK). The research findings indicate that the implementation of inclusive education still faces significant challenges, such as the absence of specific policies, an unstandardized PPDB process, an unadapted curriculum, limited facilities, a lack of teacher training, and minimal collaboration with external parties. These findings indicate the need to strengthen the management of inclusive education, improve the quality of human resources, provide adequate facilities, and strengthen collaboration with parents and external parties. This study recommends the development and implementation of comprehensive inclusive policies and the improvement of teacher competency through continuous training.